Study Coordination Design of Over Current Relay on The Kiln Area Electrical System - Putri, Raihan; Juliadi, Endri; Jannah, Misbahul; Ramji, D. R.; Al-Ani, Waleed Khalid Ahmed (Journal of Renewable Energy, Electrical, and Computer Engineering, 2021)
PT. Semen Padang is one of the largest cement producers in western Indonesia, along with the development of the cement industry PT. Semen Padang added a new Indarung VI factory to support the production process to meet market demand. With the addition of this new factory, a good safety design is needed in the design of the electrical system so that production continuity is not disturbed and reliability values are high. Therefore, over-current protection coordination studies are needed on the electrical system of the kiln area at Trafo 2 Indarung VI PT. Semen Padang to get a safe and reliable system. In the final task, this time will be done modeling, simulation of load flow and short circuit, calculation of relay settings, and simulation of coordination of overcurrent protection phase interference in the electrical system kiln area in Transformer 2 Factory Indarung VI PT. Semen Padang. The plot results of the coordination of the time flow curve obtained through the results of analysis and manual calculations recommended tuning pick-up overcurrent relayand grading time overcurrent relaytuning phase interference. Grading time between overcurrent relay is coordinated by 0.2 seconds. With the protection coordination setting, the electrical system of the kiln area at the Indarung VI factory PT. Semen Padang is safer and more reliable.